2012
DOI: 10.1017/s0032247412000198
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating the Arctic and the Arctic Council: pre-emption, precaution and preparedness

Abstract: This paper considers the role of the Arctic Council (AC) and its relationship to the future or even futures. Factors such as sea ice thinning and melting permafrost, alongside globalisation, have been cited as consequential in transforming the Arctic region. While we might be cautious about the novelty of change per se, there is a need for further debate about how the 'future' is imagined and put into practice. Exploring different logics, including precaution, pre-emption and preparedness, consideration is off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…Clusters give an opportunity to build a system of spreading new knowledge, contribute to efficient cooperation of economic entities; set new directions in business, including science-based and high-tech ones; accelerate innovation processes which is a great competitive advantage of the region. [16][17][18]. Taking into account the defined priorities of AZRF socio-economical development, the focus is put upon clusters of the following enterprises: information and communication technology, radionics and instrument-making, oil and gas processing, geological exploration, industrial mechanic engineering, mining industry, iron and steel industry, shipbuilding, nuclear and radiation technology, environment preservation.…”
Section: Resultsmentioning
confidence: 99%
“…Clusters give an opportunity to build a system of spreading new knowledge, contribute to efficient cooperation of economic entities; set new directions in business, including science-based and high-tech ones; accelerate innovation processes which is a great competitive advantage of the region. [16][17][18]. Taking into account the defined priorities of AZRF socio-economical development, the focus is put upon clusters of the following enterprises: information and communication technology, radionics and instrument-making, oil and gas processing, geological exploration, industrial mechanic engineering, mining industry, iron and steel industry, shipbuilding, nuclear and radiation technology, environment preservation.…”
Section: Resultsmentioning
confidence: 99%
“…Like the influence of the IPCC, the Organisation for Economic Co‐operation and Development, or the World Health Organization on a global scale, linking a policy decision or action in the circumpolar region to the Arctic Council is seen to provide that decision with immediate credibility and legitimacy. Furthermore, governance experts have taken an interest in the Council's unique and innovative governance model as something that other institutions and regions could learn from (Abele & Rodon, ; Dodds, ; Stokke, ; Young & Kankaanpaa, ). Yet very little empirical work has been undertaken to understand the governance design of the Arctic Council.…”
Section: Boundary Work Within the Arctic Councilmentioning
confidence: 99%
“…Regional studies have shown limitations in SAR capacities, including the SAR technology adapted to the region. This includes information and communication tools for remote areas such as Single Window (Fjortoft et al 2011), innovation in Arctic vessel and rescue equipment (Berg et al 2013;Gudmestad and Karunakaran 2012;Torheim and Gudmestad 2011) and development of Arctic infrastructure (Dodds 2013). There is a need for operational knowledge, especially on cooperation among the broad range of actors involved in major accidents, including the crew of the vessel in distress, joint rescue coordination centers (JRCC), coast guard, private preparedness organizations, Samaritan vessels, police, the ship owners and their stakeholders .…”
Section: Introductionmentioning
confidence: 99%